Аппроксимация формы импульсных токов при задании контролируемых параметров и интеграла действия - Петков, Александр Александрович (НТУ "ХПИ", 2008)
In work the problem of the form current impulse approximation specified by a combination of amplitude-time parameters and action integral is considered. Expressions for the description A-components of an lightning current impulse are received
Keywords: импульсный ток; контролируемые параметры; интеграл действия